Factors Affecting Financial Distress of the Companies in Consumer Cyclical Sector - Indri Sindia Hantika; Cindy Henciana; Tika Septiani (Облік і фінанси)
If a company cannot face business competition, it will eventually experience losses. Later, this can potentially cause some business entities to face solvency problems. When a business has difficulty making ends meet, it is called financial distress. Previous studies have provided quite mixed results regarding the factors affecting financial distress. For this reason, based on a quantitative approach, this study aimed to determine how liquidity (proxied by the current ratio), leverage (proxied by the debt-to-asset ratio), and company size influence the financial distress of companies in the consumer cyclical sector. This study utilizes secondary data, including annual reports and financial statements obtained from the official website of the Indonesia Stock Exchange (IDX) (www.idx.com). The study covers a three-year period, focusing on the financial performance of companies in the consumer cyclical sector. Researchers apply liquidity ratio, leverage ratio, and company size as independent variables and financial distress as the dependent variable. Data processing used regression analysis implemented through IBM SPSS Statistics software version 21, including descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the data analysis show that the liquidity proxied by the current ratio is not related to financial distress. There is no negative correlation between financial distress and the leverage proxied by the debt-to-asset ratio. However, financial distress has a negative correlation with company size. Although this study's results did not confirm two of the three hypotheses identified by the researchers, the financial ratios considered in the work have essential significance for assessing the company's financial condition.